Log supply in Peninsular Malaysia : is there a real cause for concern? - Mohamed, Shukri (Forest Research Institute Malaysia, 2008)
The future of the wood-based industry in Peninsular Malaysia is at stake as the industry is facing yet another general shortage of log supply. This paper analysed the log supply situation by comparing log production and domestic demand for logs in Peninsular Malaysia from 1990 to 2006. By year 1999, local demand for logs exceeded production. The gap would probably widen in the future as log production is expected to maintain its downward trend due to reduction in total forest lands harvested, decline in yield of log production, and irregular production of logs from rubber and forest plantations. Peninsular Malaysia will have to be dependent not only on the import of logs but also other wood-based products in the future.